Intrahepatic cholangiocarcinoma with aberrant hepatic artery presenting as hepatic abscess: a case report - Li, Bing; Wang, Jingyuan; Gong, Jianping (International Surgery Journal, 2020)
Intrahepatic cholangiocarcinoma (ICC) is a primary hepatic malignancy that originates from epithelial cells of bile duct. Lack of diagnostic measures and therapies leads to an increasing number of deaths from ICC worldwide. Here we described a case of 61-year-old Chinese female, who initially presented with right upper quadrant pain, combined with the results that a low density mass accompanied by multiple nodules occupied the right liver lobe by CT-scan, which also showed an aberrant right hepatic artery that participated in the right liver lobe and origining from the superior mesenteric artery, this patient was clinically considered as hepatic abscess (HA). The patient’s right upper quadrant pain was alleviated after been treated with the infusion chemotherapy of the aberrant right hepatic artery (ARHA) via percutaneous femoral arterial catheterization by Seldinger technique (Meropenem 7 days) following the failure of the liver-puncture drainage. However, the right upper quadrant pain occurred again 6 days later, serum CA19-9>1000.0 U/ml, which indicated the possibility of hepatic malignancy, so we performed laparotomy. The histopathological result of intraoperative frozen section demonstrated cholangiocarcinoma, unfortunately, it was unresectable. Finally, right lower lung pneumonia and pleural empyema happened to her and she succumbed to respiratory failure 22 days following surgery. In this report, we will discuss the case with reference to the literature.